2016
DOI: 10.1007/s10531-016-1128-4
|View full text |Cite
|
Sign up to set email alerts
|

The network BiodiversityKnowledge in practice: insights from three trial assessments

Abstract: In order to develop BiodiversityKnowledge, a Network of Knowledge working at the European science-policy interface for biodiversity and ecosystem services, we conducted three trial assessments. Their purpose was to test structure and processes of the knowledge synthesis function and to produce knowledge syntheses. The trial assessments covered conservation and management of kelp ecosystems, biological control of agricultural pests, and conservation and multifunctional management of floodplains. Following the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…For this first step, we built on results from three test cases (on three areas of knowledge: kelp ecosystems, agricultural pest control, and multifunctional floodplain management, see Schindler et al 2016) as well as on the internal self-evaluation concluded within KNEU at that time (see Carmen et al 2015). In a second step, we organised a one and a half day expert workshop in January 2014, with participants from KNEU and several SPI experts from different European countries who were not involved in the KNEU project and who had experience on SPIs in the environmental sector.…”
Section: Methods: Consultations and Debate On Governance Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this first step, we built on results from three test cases (on three areas of knowledge: kelp ecosystems, agricultural pest control, and multifunctional floodplain management, see Schindler et al 2016) as well as on the internal self-evaluation concluded within KNEU at that time (see Carmen et al 2015). In a second step, we organised a one and a half day expert workshop in January 2014, with participants from KNEU and several SPI experts from different European countries who were not involved in the KNEU project and who had experience on SPIs in the environmental sector.…”
Section: Methods: Consultations and Debate On Governance Optionsmentioning
confidence: 99%
“…The knowledge synthesis function was extensively studied within the project, whereby a prototype procedure was set up (Livoreil et al 2016) and tested in three trial assessments (Schindler et al 2016). The design that was chosen envisaged a structured approach, flexible in the choice of appropriate methods with a strong emphasis placed upon specifying the question and choosing appropriate methodologies jointly with the requester and relevant stakeholders to transcend the linear model of scientific policy advice.…”
Section: Methods: Consultations and Debate On Governance Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue is based on the project's work and brings together a number of papers that investigate functions, processes and solutions for such a Network of Knowledge. The prototype of the NoK called ''BiodiversityKnowledge'' was installed during the KNEU project and carried out a number of trial assessments in different areas of biodiversity and ecosystem services (Schindler et al 2016a). The papers thus offer a concise overview of the challenges and opportunities that such flexible approaches of networking knowledge holders and requesters provide beyond the well-established approaches at the interface between science, policy and society.…”
Section: Challenges and Solutions For Networking Knowledgementioning
confidence: 99%
“…1). Schindler et al (2016a) present an overview of the results and practical lessons learned of these trial assessments. A further evaluation of the trial assessments and how a Network of Knowledge would support them is presented in Carmen et al (2015).…”
Section: Challenges and Solutions For Networking Knowledgementioning
confidence: 99%